Haematobiochemical Alterations and Pathological Lesions Induced by Fasciolosis in Slaughtered Cattle at Gondar ELFORA Abattoir, Northwest Ethiopia - Abraham Belete Temesgen; Tadegegn Mitiku; Mastewal Birhan; Mersha Chanie Kebede; Mohammed Yesuf; Muluken Yayeh Mekonnen; Moges Maru Alemayehu; Birhan Anagaw Malede; Abdo Megra Geda; Aregash Wendimu Tumebo; Kefale Ambachew Shiferaw; Zerihun Getie Wassie; et al. (Veterinary Medicine and Science, 2025)
ABSTRACT Fasciolosis is a neglected zoonotic parasitic disease caused by Fasciola hepatica and Fasciola gigantica. It is a serious public health and veterinary concern, with significant consequences for both human and livestock populations. An abattoir‐based cross‐sectional study was conducted from January to September 2023 at Gondar ELFORA Abattoir, Northwest Ethiopia, to assess haematobiochemical alterations and pathological lesions induced by fasciolosis in slaughtered cattle. The study included one hundred apparently healthy male local‐breed cattle, divided into two groups of fifty: one infected and one non‐infected. Cattle were selected using a purposive sampling technique. Infected cattle showed significantly lower mean values for haemoglobin (HGB), haematocrit (HCT), mean corpuscular volume (MCV), total erythrocyte count (TEC), lymphocytes, monocytes, total protein, albumin and glucose compared to non‐infected cattle. Conversely, they had higher mean values for mean corpuscular haemoglobin concentration (MCHC), total leukocyte count (TLC), neutrophils, eosinophils, aspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (ALP). Basophil levels were similar in both groups. Liver alterations observed in acute fasciolosis included hepatomegaly with rounded edges and the presence of juvenile flukes within the parenchyma, while in chronic fasciolosis, the liver appeared smaller and firm, with a corrugated capsule and dilated bile ducts containing twisted flukes. Microscopically, acute fasciolosis showed eosinophil infiltration, hemosiderin pigmentation and congestion around the central vein and sinusoids, whereas chronic fasciolosis showed fibrosis, bile duct proliferation, and metaplasia of epithelial cells from columnar to cuboidal. The observed findings indicate a severe hepatic and systemic disease process driven by parasitic infection, resulting in significant compromise of the cattle's health. Therefore, regular screening and effective deworming are essential to control bovine fasciolosis, especially in high‐risk abattoirs. Haematology and biochemical tests should be part of routine diagnosis for early detection and liver function assessment, while histopathology confirms the infection stage. Enhancing stakeholder awareness and training is vital and further research on seasonal patterns, risk factors and drug resistance is needed to improve control strategies.